Blockchain-Oriented Software Variant Forks: A Preliminary Study - Rocha, Henrique; Businge, John (IEEE, 2022)
In collaborative social development platforms such as GitHub, forking a repository is a common activity. A variant fork wants to split the development from the original repository and grow towards a different direction. In this preliminary exploratory research, we analyze the possible reasons for creating a variant fork in blockchain-oriented software. By collecting repositories in GitHub, we created a dataset with repositories and their variants, from which we manually analyzed 86 variants. Based on the variants we studied, the main reason to create a variant in blockchain-oriented software is to support a different blockchain platform (65%).
Keywords: Blockchain-oriented software; BOS; Variant forks; Hard forks; Software family